Optimizing the Role of the Intelligence and Security Unit in Early Detection to Prevent Illicit Drug Circulation in Pekalongan Resort Police - Zaidan, Omar (Advances in Police Science Research Journal, 2024)
Drugs trafficking is classified as one of organized crime. Intelligence and Security Unit (“Satintelkam”) has an important role to fill in doing preventive measures such as controlling and monitoring illicit drugs circulation with clandestine principal held throughout entire investigation. Hence, early detection becomes pivotal in war against drugs. The increasing number of illicit drugs crimes indicates the suboptimal role of Satintelkam in preventing the illicit drugs circulation in Pekalongan. This study identified the challenges faced by Satintelkam of the Pekalongan Police Resort, analyzed them, and attempted to provide solutions to optimize the role of the Satintelkam in preventing illicit drugs circulation. The study employed a qualitative approach with a field research method. The research aimed to explore and uncover facts (exploratory), in order to provide a descriptive picture of the early detection efforts carried out by Satintelkam of the Pekalongan Police Resort to prevent the illicit drugs circulation. The data were collected through interviews, observation, and document analysis. The obtained data were analyzed using the SWOT analysis theory and management theory. The research was enriched with the concepts of crime prevention, security intelligence, early detection, Polri PRESISI, Criminal Intelligence and Management Intelligence Unit - United Nations on Drugs and Crime (UNODC), and the illicit drugs circulation based on Narcotics Law. The research findings indicate that the role of Satintelkam of the Pekalongan Police Resort is not optimal. The study observed several conditions, namely: (a) Satintelkam focus on certain operational tasks resulting there is no routine activities for early detection and prevention of illicit drugs circulation; (b) Satintelkam tasks intersect with those of other units; (c) early detection efforts are not in accordance with the procedures; (d) the lack of personnel quantity in Satintelkam; (e) the minimal capability of personnel to use special tools in investigative operations. This research provides recommendations to optimize the role of Satintelkam, including: (a) active cooperation with other functional units, various community elements, and relevant agencies; (b) increasing the quantity of personnel; (c) improving personnel capabilities in applicating more modern and effective investigation methods and technologies.